Form and Formulation: Examining the Distinctiveness of Body Image Constructs in Treatment- Seeking Patients with Binge-Eating Disorder - Lydecker, Janet A. (J Consult Clin Psychol, 2017)
OBJECTIVE: Body-image disturbance is a core aspect of eating disorders, yet the clinical manifestations of individuals’ weight and shape concerns are complex, vary considerably, and are poorly understood by clinicians and researchers. This study aimed to distinguish different aspects of body-image disturbance – including weight/shape dissatisfaction, weight/shape overvaluation, weight/shape preoccupation, and fear of weight gain – in patients with binge-eating disorder (BED). Examining how each specific body image construct relates to biopsychosocial features of BED could contribute to the refinement of conceptualization and treatment planning. METHOD: The current study assessed body-image disturbance and eating-disorder psychopathology in 748 treatment-seeking patients with BED using established investigator-based interviews reliably administered by doctoral clinicians. RESULTS: The four body image constructs, although related to one another, showed some important similarities in associations with biopsychosocial clinical features, as well as some important distinctions. The relation between overvaluation and self-esteem was, as conceptualized, more strongly negative than for other body image variables, and preoccupation was more associated than other body image variables with eating concerns. Biopsychosocial features of BED were associated with different forms of body-image disturbance, but associations of body image variables with BMI were not significant and associations with binge-eating frequency did not differ across body image variables. CONCLUSION: Manifestations of body-image disturbance in BED are complex and understanding the distinctions between different body image constructs can contribute to treatment formulation.